Theranostics: Polymer Capsules as a Theranostic Tool for a Universal In Vitro Screening Assay—The Case of Lysosomal Storage Diseases (Part. Part. Syst. Charact. 11/2015). (November 2015) - Nazarenus, Moritz; Abasolo, Ibane; García‐Aranda, Natalia; Voccoli, Vladimir; Rejman, Joanna; Cecchini, Marco; Schwartz, Simó; Rivera_Gil, Pilar; Parak, Wolfgang J.
Abstract : Polymer multilayer capsules are used by P. Rivera_Gil, W. J. Parak, and co‐workers for concomitant pH‐sensing and enzyme delivery to lysosomes in the framework of enzyme‐replacement therapy in lysosomal‐storage disorders, as described on page 991. The capsules act as local reporters of the pH by changing the fluorescence of the carried sensor from red (alkaline) to yellow (acidic) upon endocytosis and organelle acidification. In the acidic lysosomes, the capsules deliver the enzyme to substitute the defective one.